A new analytical model for photo-dependent capacitances of GaAs MESFET's with emphasis on the substrate related effects - Narasimha Murty N.V.L.; Jit S. (My University, 2025)
A new analytical model for optical and bias dependent nonlinear capacitances of GaAs MESFET which is valid for both linear and saturation regions has been proposed in this paper. The novelty lies in modeling of internal and external photovoltaic effects that includes deep level traps in the substrate and surface recombination at metal-semiconductor interface of the gate. The effect of high field domain formation at the drain end in the saturation region has also been included to improve the accuracy of the present model. The model presents backgating effects on gate-source and gate-drain capacitances of GaAs MESFET for the first time in literature. Finally, the proposed model has been compared to the reported results to show the validity. The proposed model may be very useful for the designing of photonic MMIC's and optical receivers using GaAs MESFET's. © 2006 Elsevier Ltd. All rights reserved.